(untitled) (SCIENCE TIME JOURNAL, 2026)
The article deals with the theoretical and methodological foundations of Content and Language Integrated Learning (CLIL) as a pivotal technology in modern education. The author explores how the formation of a unified global space has shifted the focus from traditional language learning to a dual-oriented approach that integrates subject matter and foreign language proficiency. The study highlights the "4C" principle (Content, Communication, Cognition, and Culture) and David Coyle’s "Language Triptych" as essential frameworks for developing students’ cognitive and communicative skills. Particular emphasis is placed on the development of High-Order Thinking Skills (HOTS) and Cognitive Academic Language Proficiency (CALP). The article concludes that CLIL not only enhances linguistic competence but also fosters a deeper understanding of native language semantics and cultural awareness.